2019
DOI: 10.1111/iej.13140
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 activation induces expression of the pro‐inflammatory mediator Urokinase Plasminogen Activator via NF‐κB and MAPK signalling pathways in human dental pulp cells

Abstract: Aim To explore the involvement of TLR5 in pulp inflammation and to examine the effects of TLR5 activation with its ligand, FlaB protein, on pro‐inflammatory gene expression. Methodology TLR5 expression in dental pulp tissues and human dental pulp cells (hDPCs) were determined by immunohistochemistry, immunocytochemistry, Western blots and RT‐PCR analyses. To examine the role of TLR5, hDPCs were treated with recombinant FlaB protein (500 ng mL−1) to activate the receptor or with a small interfering RNA against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Activation of TLR can stimulate mitogen-activated protein kinases (MAPK) signaling pathways in addition to intracellular NF-κB, inducing the expression of a variety of inflammatory factors [ 46 ]. Before verifying that the KRG is involved in the MAPK pathway, we confirmed that MAPK is activated by DEHP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of TLR can stimulate mitogen-activated protein kinases (MAPK) signaling pathways in addition to intracellular NF-κB, inducing the expression of a variety of inflammatory factors [ 46 ]. Before verifying that the KRG is involved in the MAPK pathway, we confirmed that MAPK is activated by DEHP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation by flagellin, TLR5 engages with its adaptor protein MYD88, leading to the activation of the NF-κB pathway, which plays a role in the transcriptional regulation of TWIST1. 22 , 41 TWIST1 is a crucial transcription factor in EndMT and regulates the expression of EndMT-related proteins, including N-cadherin and E-cadherin. 42 Our results suggested that E coli might regulate EndMT in LSECs through the TLR5/MYD88/NF-κB/TWIST1 pathway via flagellin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the IL-1β-induced decline of PAI-1 can be prevented by SB203580, but not by U0126, 5Z-7oxozeaenol, or LY294002, implicating the possible differential regulation of signaling pathways. TLR5 is shown to stimulate uPA in HDPCs via NF-kB, MEK/ERK, and p38 signaling [ 10 ]. Targeting therapy via the suppression of these signaling molecules may be useful to control tissue inflammation and the fibrinolytic activities of the dental pulp in the future.…”
Section: Discussionmentioning
confidence: 99%
“…PA promotes cell migration and proliferation and is involved in numerous physiological and pathological conditions, such as inflammation and tissue remodeling [ 9 ]. TLR5 activation may stimulate uPA in HDPCs [ 10 ]. The expression of tPA is elevated in inflamed dental pulp relative to healthy dental pulp [ 11 ].…”
Section: Introductionmentioning
confidence: 99%